2008
DOI: 10.1016/j.brainres.2008.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Rapid eye movement (REM) sleep homeostatic regulatory processes in the rat: Changes in the sleep–wake stages and electroencephalographic power spectra

Abstract: The aim of this study was to elucidate physiological processes that are involved in the homeostatic regulation of REM sleep. Adult rats were chronically instrumented with sleep-wake recording electrodes. Following post-surgical recovery, rats were habituated extensively for freely moving polygraphic recording conditions. On the first experimental recording day (baseline day, BLD), polygraphic signs of undisturbed sleep-wake activities were recorded for 4 h (between 11:00 AM and 3:00 PM). During the second expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 56 publications
7
41
0
Order By: Relevance
“…Stress increased REM sleep (p <0.005), but RGE unfortunately did affect these changes REM sleep. Our results are consistent with ginseng's effects in ameliorating stress-related sleep disorders, particularly by changing the balance of NREM and REM sleep (Bjorvatn et al, 1998;Shea et al, 2008). These results suggest that RGE may be useful for treatment of stress-related disorders.…”
Section: Discussionsupporting
confidence: 86%
“…Stress increased REM sleep (p <0.005), but RGE unfortunately did affect these changes REM sleep. Our results are consistent with ginseng's effects in ameliorating stress-related sleep disorders, particularly by changing the balance of NREM and REM sleep (Bjorvatn et al, 1998;Shea et al, 2008). These results suggest that RGE may be useful for treatment of stress-related disorders.…”
Section: Discussionsupporting
confidence: 86%
“…12 and this study) along with other measures of REM sleep behavior, such as higher REM sleep episode number and shortened REM sleep latency (12). This pattern is different from that observed in acute sleep deprivation in which REM sleep rebound positively correlates with sleep pressure (9,10). In CSR, daily accumulation of REM sleep loss [∼1.5 h/d (11)] did not lead to progressive increasing REM sleep rebound.…”
Section: Discussionmentioning
confidence: 59%
“…REM sleep shows strong homeostatic regulation; acute losses are compensated by rebounds proportional to the lost amount of REM sleep (9,10). However, recent studies using the CSR paradigm, which better resembles common human sleep loss (11,12), revealed limitations of this mechanism, demonstrating that after the first day of sleep loss, REM sleep rebound settles on a persistent elevated level and does not show a progressive increase over days as REM sleep debt keeps accumulating.…”
mentioning
confidence: 99%
“…S8B). In previous studies (37,38) an increased ratio SWA to alpha/theta during REM sleep was suggested to reflect the buildup of REM pressure, but during our SR experiment this ratio either did not change (frontal and occipital cortex) or increased, but not progressively (parietal cortex). Large increases in REM sleep were also present after SR and as a result, almost all REM sleep lost during SR was recovered by the end of the second post-SR day (Fig.…”
Section: ) (C) 4smentioning
confidence: 61%